Wearable Psychological Stress Monitoring Equipment and Data Analysis Based on a Wireless Sensor. (9th June 2022) - Xu, Huixiang; Zhang, Nan; Liu, Qiuju
Abstract : With the rapid development of social economy, human psychological pressure is an important factor affecting human health. Excessive psychological pressure will lead to serious psychological diseases such as depression and anxiety. The traditional psychological stress monitoring method is mainly limited to the psychological scale. This method has a certain subjectivity, so its corresponding test data is not representative. At the hardware design level, this paper will select miniaturized, low-power, and low-cost microphysiological sensors to monitor the psychological pressure level discrimination indicators such as heart rate, body temperature, and heart rate waveform and fully optimize the layout of wireless sensors at the hardware layout level to achieve the high efficiency of the whole system. The detection of human pulse signal and heart rate signal is mainly carried out through microsensors, and the temperature signal is filtered and amplified, and analog-to-digital conversion is carried out to realize the accurate measurement of key signal waveform. At the level of hardware system and software algorithm, this paper creatively proposes a psychological stress recognition algorithm based on evidence theory. By extracting the collected key signal features, we can identify the primary stage of psychological stress and finally realize the evaluation and analysis of individual psychological stress through evidence theory. The experimental results show that the trust degree of an individual psychological stress test is improved by 0.187 compared with the traditional algorithm, and the corresponding psychological stress trust degree is up to 0.988, which has obvious advantages.